Ecological distribution of honeybee chalkbrood disease (Ascosphaera Apis) in EthiopiaEcological distribution of honeybee chalkbrood disease (Ascosphaera Apis) in Ethiopia - Yohannes, A.; Bezabeh, A.; Yaekob, B.; Begna, D.; Shiferaw, Y.; Kebede, Y.; Kebede, N. (2009)
Sheko is the only surviving taurine of the Abyssinian region, and is in danger ofextinction mainly due to interbreeding with neighboring Zebu breeds and scarcityof pure Sheko breeding bulls. This study was undertaken to study current statusof Sheko cattle breed and husbandry practices in southwestern Ethiopia betweenAugust 2004 and February 2005. The survey revealed that farmers do recognizespecial characteristics and desirable qualities of the breed, notably its tolerance toendemic diseases, the relative high milk yield, long lactation period, stamina fortraction, less selective feeding behavior and maintaining good body condition attimes of feed scarcity. The breed’s voracious feeding habit and aggressive temperament,however, are noted by farmers as undesirable traits. To reverse the decliningpopulation trend and to lay the elements of sustainable use, a breed managementplan consisting of establishing in situ breeding station, organizing a Shekocattle owners’ society, establishing breed studs in its breeding tract, promotingniche market and improving the husbandry practices, were proposed.Sheko is the only surviving taurine of the Abyssinian region, and is in danger ofextinction mainly due to interbreeding with neighboring Zebu breeds and scarcityof pure Sheko breeding bulls. This study was undertaken to study current statusof Sheko cattle breed and husbandry practices in southwestern Ethiopia betweenAugust 2004 and February 2005. The survey revealed that farmers do recognizespecial characteristics and desirable qualities of the breed, notably its tolerance toendemic diseases, the relative high milk yield, long lactation period, stamina fortraction, less selective feeding behavior and maintaining good body condition attimes of feed scarcity. The breed’s voracious feeding habit and aggressive temperament,however, are noted by farmers as undesirable traits. To reverse the decliningpopulation trend and to lay the elements of sustainable use, a breed managementplan consisting of establishing in situ breeding station, organizing a Shekocattle owners’ society, establishing breed studs in its breeding tract, promotingniche market and improving the husbandry practices, were proposed.